2021
DOI: 10.1038/s41598-021-97932-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of nitrogen-doped functional groups and porosity of porous carbons on electrochemical performance of supercapacitors

Abstract: In this work, nitrogen-doped porous carbons obtained from chitosan, gelatine, and green algae were investigated in their role as supercapacitor electrodes. The effects of three factors on electrochemical performance have been studied—of the specific surface area, functional groups, and a porous structure. Varying nitrogen contents (from 5.46 to 10.08 wt.%) and specific surface areas (from 532 to 1095 m2 g−1) were obtained by modifying the carbon precursor and the carbonization temperature. Doping nitrogen into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…From the XPS analysis, it was confirmed that the prepared samples mainly consisted of oxygen functional groups with trace amounts of nitrogen functionalities on the carbon framework. It is generally observed that activated carbon with O, N‐ heteroatoms play a positive role in providing additional pseudocapacitance, hydrophilicity, and promotes electron transfer rate of the electrode material 67,75,76 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the XPS analysis, it was confirmed that the prepared samples mainly consisted of oxygen functional groups with trace amounts of nitrogen functionalities on the carbon framework. It is generally observed that activated carbon with O, N‐ heteroatoms play a positive role in providing additional pseudocapacitance, hydrophilicity, and promotes electron transfer rate of the electrode material 67,75,76 …”
Section: Resultsmentioning
confidence: 99%
“…It is generally observed that activated carbon with O, N-heteroatoms play a positive role in providing additional pseudocapacitance, hydrophilicity, and promotes electron transfer rate of the electrode material. 67,75,76…”
Section: Compositional Analysismentioning
confidence: 99%
“…The above set of results suggests that TAC3 has various O-containing and N-containing groups on the surface. Importantly, these functional groups can effectively improve the hydrophilicity and wettability of activated carbon, thus making the surface accessible to aqueous electrolytes and capable of excellent electrochemical performances [ 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reports on the use of N-doped ACs as active electrode materials for aqueous SCs show capacitance values between 150 and 250 F g − 1 , depending on the nitrogen content of the AC, the applied current densities and the electrolyte selected [8,12,[23][24][25]. However, in symmetric devices, the relatively high C sp values achieved do not improve to a high extent the energy and power densities.…”
Section: Introductionmentioning
confidence: 99%